Assessment of Informal Settlement in Central Kandahar: A Case Study of Area Within Four Historic Gateways - PASHTON, Numan; NOORZAI, Mohammad Qasim (Journal for Research in Applied Sciences and Biotechnology, 2024)
Afghanistan's post-war recovery, commencing in 2001 following the cessation of hostilities, precipitated rapid urbanization, notably witnessed by a substantial proliferation of informal settlements, primarily concentrated in Kandahar Province. This phenomenon, exacerbated by significant rural-to-urban migration and population expansion, has emphasized the imperative for exhaustive research aimed at comprehensively understanding its definitions, associated types and potential impacts of informal settlement. The proliferation of informal settlements in Kandahar's historic gateways presents a complex challenge necessitating meticulous and nuanced analysis. The research endeavors to undertake a comprehensive exploration of the definitional constructs of informal settlements, encompassing diverse typologies and their ramifications on urban settings. Central to this endeavor are key objectives aimed at scrutinizing squatter settlements, discerning their typologies, including Spontaneous Sheltering, Homeless Encampments, Nomadic Tents, Refugee Camps, Carts and Wagons, Squatter Settlements, Slums, Self-Help Housing, Shantytowns, Informal Subdivisions and Tenement Housing. Furthermore, the research aims to assess the effects associated with informal supplementary settlements, which encompass a broad spectrum of socioeconomic and environmental ramifications, such as Overcrowding, Poor Living Conditions, High Levels of Poverty, Limited Basic Services, Social Marginalization, Health Risks, Inadequate Sanitation Facilities and Vulnerability. Employing a mixed-methods approach integrating field observations, surveys, Case Studies and literature review, the research seeks to comprehensively understand the complexities of informal settlement dynamics, thus providing insights for informed policy formulation and interventions in urban planning.